Bioinformatics and In Silico Findings Uncover Bio-Targets of Calycosin Against Heart Failure and Diabetes Mellitus - Xu, Hongyuan; Qin, Jingru; Qin, Lixiu; Guo, Chao; Yang, Bin (Frontiers in Endocrinology, 2022)
Background Heart failure (HF) and diabetes mellitus (DM) are life-threatening diseases. However, existing clinical drugs to treat HF complicated with DM are relatively limited. In this study, we performed a viable bioinformatics strategy combining network pharmacology and molecular docking to identify potential anti-HF and -DM targets and therapeutic mechanisms of calycosin, a functional phytoestrogen. Methods Web-based databases were used to collect candidate genes/targets of calycosin and HF/DM and then identify hub bio-targets of calycosin against HF/DM. Using the online-available database, all functional processes and signaling pathways of calycosin against HF/DM were screened and identified before further visualization. Results All potential bio-targets of calycosin and HF/DM were collected, and 20 hub targets of calycosin against HF/DM were identified. Interestingly, molecular docking findings indicated that mitogen-activated protein kinase-1 (MAPK1), β-Arrestin 1 (ARRB1), and homologue-1 (ABL1) may be potent pharmacological targets of calycosin against HF/DM. In addition, all primary molecular functions of calycosin against HF/DM were identified, including regulating protein binding, ubiquitination, and metabolic process. Furthermore, the top molecular pathways of calycosin against HF/DM were revealed, including cardiomyocyte and chemokine signaling pathways. Conclusion Our bioinformatics analysis uncovered the network targets and therapeutic mechanisms of calycosin against HF/DM. For the first time, the current in silico findings revealed that the identified hub targets may be used to screen and treat HF/DM.